2013
DOI: 10.3389/fpsyg.2013.00360
|View full text |Cite
|
Sign up to set email alerts
|

In pursuit of off-task thought: mind wandering-performance trade-offs while reading aloud and color naming

Abstract: The present study investigated whether the frequency of probe-caught mind wandering varied by condition and had any impact on performance in both an item-by-item reading aloud task and a blocked version of the classic Stroop task. Across both experiments, mind wandering rates were found to be quite high and were negatively associated with vocal onset latencies and error rates across conditions. Despite this however, we observed poor correspondence between the effects of task demands on mind wandering rates and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 53 publications
(81 reference statements)
3
68
0
Order By: Relevance
“…That is, the order of the response options or the direction of the scale must have been counterbalanced between participants, as in Christoff, Gordon, Smallwood, Smith, and Schooler (2009), in which Bsubjects answered using a 7-point Likert scale, ranging from 'completely on task' to 'completely off task'…(with the scale direction counterbalanced across subjects)^(p. 8720). Eight studies across six different articles and four different labs met both of these criteria (Christoff et al, 2009;Thomson, Besner, & Smilek, 2013;Thomson, Seli, Besner, & Smilek, 2014;Ward & Wegner, 2013;Ye, Song, Zhang, & Wang, 2014; see Table 1a). Five additional studies across four different articles and three different labs (Dixon & Bortolussi, 2013, Exp.…”
Section: Resultsmentioning
confidence: 99%
“…That is, the order of the response options or the direction of the scale must have been counterbalanced between participants, as in Christoff, Gordon, Smallwood, Smith, and Schooler (2009), in which Bsubjects answered using a 7-point Likert scale, ranging from 'completely on task' to 'completely off task'…(with the scale direction counterbalanced across subjects)^(p. 8720). Eight studies across six different articles and four different labs met both of these criteria (Christoff et al, 2009;Thomson, Besner, & Smilek, 2013;Thomson, Seli, Besner, & Smilek, 2014;Ward & Wegner, 2013;Ye, Song, Zhang, & Wang, 2014; see Table 1a). Five additional studies across four different articles and three different labs (Dixon & Bortolussi, 2013, Exp.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Feng et al (2013) and Dixon and Bortolussi (2013) found that mind wandering increases when an individual is reading difficult texts. In contrast, the data from Antrobus et al (1966), Filler and Giambra (1973), McKiernan et al (2006), Smallwood et al (2003), Teasdale et al (1995), and Thomson et al (2013) all suggest that mind wandering decreases as task difficulty and demand increase. Our data provide a potential reconciliation for these seemingly contradictory findings.…”
Section: Task Difficulty and Mind Wanderingmentioning
confidence: 91%
“…Many conflicting findings exist in the literature, some of which suggest that mind wandering increases with task difficulty (Dixon & Bortolussi, 2013;Feng et al, 2013), whereas others suggest the opposite (Antrobus et al, 1966;Antrobus, Coleman, & Singer, 1967;Filler & Giambra, 1973;Grodsky & Giambra, 1990-1991McKiernan, D'Angelo, Kaufman, & Binder, 2006;McVay & Kane, 2012;Smallwood, Obonsawin, & Reid, 2003;Teasdale et al, 1995;Thomson, Besner, & Smilek, 2013). For example, Feng et al (2013) and Dixon and Bortolussi (2013) found that mind wandering increases when an individual is reading difficult texts.…”
Section: Task Difficulty and Mind Wanderingmentioning
confidence: 99%
“…Research on mind-wandering has seen a massive increase in recent years, spreading to a wide variety of psychological domains including those examining cognition [110], neuroscience [1116], education [1720], creativity [21,22], clinical populations [2326], and workplace functioning [27], to name a few. The rapidly growing body of research on mind-wandering was largely stimulated by Smallwood and Schooler’s [28] integrative review of related concepts such as ‘task-unrelated imagery and thoughts (TUITs)’ [29] and ‘stimulus-independent thought’ [30].…”
Section: The Intentionality Of Mind-wanderingmentioning
confidence: 99%